SaaS sRNA promotes the interfering effect of Salmonella on hepatic iron metabolism via modulating ferroportin 1 - Linlin Cai; Yunting Xie; Haijing Hu; Chongyang Lv; Liangting Shao; Huhu Wang; Xinglian Xu; Guanghong Zhou (iScience)
Summary: Iron limitation plays a fundamental role in host immunity against Salmonella infection. The mechanisms by which Salmonella antagonizes nutritional immunity, particularly those regulated by small non-coding RNAs (sRNAs), remain incompletely understood. In this study, we investigated the role of a previously identified sRNA, Salmonella adhesive-associated sRNA (SaaS), in host iron metabolism. Utilizing a combined BALB/c mouse model and HepG2 cell model, we demonstrated that SaaS enhances hepcidin synthesis via the bone morphogenetic protein (BMP)-SMAD pathway, leading to decreased ferroportin 1 level. This suppression of ferroportin 1 results in reduced serum iron and increased hepatic iron accumulation, ultimately causing iron-deficiency anemia. The accumulation of iron triggers hepatic oxidative stress, exacerbating liver damage. Concurrently, SaaS activates the signal transducer and activator of transcription 3 (STAT3) pathway in a triggering receptor expressed on myeloid cells-1 (TREM1)-interleukin (IL)-6-dependent manner, intensifying the inflammatory response. Collectively, these results provide evidence that sRNAs serve as crucial regulators of Salmonella pathogenesis and underscore the potential of targeting sRNAs for the prevention of salmonellosis.